Asymmetric Catalysis: Asymmetric Catalysis within the Chiral Confined Space of Metal–Organic Architectures (Small 32/2019). Issue 32 (9th August 2019) - Li, Xuezhao; Wu, Jinguo; He, Cheng; Meng, Qingtao; Duan, Chunying
Abstract : In article number1804770, Chunying Duan and co‐workers comprehensively survey recent asymmetric catalysis processes of metal–organic cages (MOCs) and metal–organic frameworks (MOFs) with chiral confined space that is analogous to the binding pocket of enzymes. The spatial constraints and shielding effects exhibit an ideal working yard to accelerate a series of novel asymmetric transformations with one‐chiral center or even multi‐chiral centers by modulating the orientational and rotational freedom of the encapsulated substrates. The commonality and differences of chiral MOCs‐ and MOFs‐based asymmetric catalysis are discussed to present a connection between these two important fields and share design concepts and applications that may be useful to both in asymmetric transformations.